2012
DOI: 10.3389/fpsyg.2012.00378
|View full text |Cite
|
Sign up to set email alerts
|

Does Explicit Expectation Really Affect Preparation?

Abstract: Expectation enables preparation for an upcoming event and supports performance if the anticipated situation occurs, as manifested in behavioral effects (e.g., decreased RT). However, demonstrating coincidence between expectation and preparation is not sufficient for attributing a causal role to the former. The content of explicit expectation may simply reflect the present preparation state. We targeted this issue by experimentally teasing apart demands for preparation and explicit expectations. Expectations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Probability matching (3) is reflected in choosing alternatives according to the relative frequency with which they are rewarded. For instance, Umbach et al (2012) observed that participants predicted the stimulus that was presented in 60% of the trials in about 60% of the trials. For the stimuli presented in 30% of the trials and in 10% of the trials expectation frequencies matched presentation frequencies as well.…”
Section: The Distinction Between Self-generated and Cue-induced Expecmentioning
confidence: 96%
See 1 more Smart Citation
“…Probability matching (3) is reflected in choosing alternatives according to the relative frequency with which they are rewarded. For instance, Umbach et al (2012) observed that participants predicted the stimulus that was presented in 60% of the trials in about 60% of the trials. For the stimuli presented in 30% of the trials and in 10% of the trials expectation frequencies matched presentation frequencies as well.…”
Section: The Distinction Between Self-generated and Cue-induced Expecmentioning
confidence: 96%
“…In the cued expectation condition, the participant would be shown a gray star as cue (cf. Umbach et al, 2012) or be shown the word "star" as cue and asked to verbalize it (c.f. Kemper et al, 2012).…”
Section: From Prediction To Cues -Shift In Experimental Procedures Re-mentioning
confidence: 99%
“…Note that dissociations between prediction and preparation are possible (e.g., Jiménez & Méndez, 2013). Umbach et al (2012) showed that participants can keep up with a response deadline assigned to a less frequent stimulus while predicting the frequent stimulus to occur. Third, aftereffects of prediction (mis)match did not seem to vary with frequency: When predicting the most frequent stimulus prediction, mismatch seemed to have the same consequences for the next trial as when predicting the less frequent stimulus, despite much more likely mismatches in the latter case.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it appears that conscious expectation is not so straightforwardly dependent or subordinate as the Perruchet effect claims it is, having actually a causal role in unconscious cognitive processing, namely by contributing to unconscious preparation for action (see Umbach et al, 2012).…”
Section: Main Issuesmentioning
confidence: 99%